Equilibration in bicyclic pyroglutamates by ring opening-reclosure - Moloney, M; Yaqoob, M (2008)
Enantiopure bicyclic tetramates, readily obtained by Dieckmann ring closure on oxazolidine-derived templates, can be further converted to hydroxypyroglutamates by kinetically controlled nucleophilic additions, and some of these products are capable of equilibration via a facile retro-aldol/aldol reclosure. © 2008 Elsevier Ltd. All rights reserved.